The Pardisomus species from Costa Rica, with descriptions of four new species and one larva (Coleoptera: Curculionidae: Baridinae). - Prena, Jens (Contributions to Entomology = Beiträge zur Entomologie, 2003)
The neotropical weevil genus Pardisomus Pascoe is redefined based on morphological character states of Agalmatus Kuschel and association of six species with Pentagonia Bentham (Rubiaceae). Procholus Desbrochers, Anambates Casey, Piazambates Voss and Agalmatus are new synonyms of Pardisomus. New combinations with Pardisomus are 1) from Agalmatus: P. brasiliensis (Kuschel), P. geniculatus (Hustache), P. nigritarsis (Kuschel), P. panamensis (Kuschel); 2) from Embates: P. cleroides (Champion); 3) from Lydamis: P. squamipes (Kirsch); 4) from Peridinetus: P. rufescens (Hustache); 5) from Piazambates: P. piazuroides (Voss); and 6) from Procholus: P. biplagiatus (Desbrochers). Four new species of Pardisomus are described from Costa Rica: P. albescens, P. amotus, P. byrrus and P. suffuscus. The larva of putative P. biplagiatus is described for the first time.Keywordsweevils, taxonomy, new species, Pentagonia, Neotropics.Nomenclatural ActsAgalmatus Kuschel, 1958 (Curculionidae), syn. n. of Pardisomus Pascoe,1889Anambates Casey, 1922 (Curculionidae), syn. n. of Pardisomus Pascoe,1889Procholus Desbrochers, 1907 (Curculionidae), syn. n. of Pardisomus Pascoe,1889Piazambates Voss, 1954 (Cureculionidae), syn. n. of Pardisomus Pascoe,1889albescens Prena, 2003 (Pardisomus), spec. n.amotus Prena, 2003 (Pardisomus), spec. n.biplagiatus (Desbrochers, 1906) (Pardisomus), Lectotype; comb. n. hitherto Pseudolochus biplagiatusbrasiliensis (Kuschel, 1958) (Pardisomus), comb. n. hitherto Agalmatus brasiliensisbyrrus Prena, 2003 (Pardisomus), spec. n.cleroides (Champion, 1907) (Pardisomus), Lectotype; comb. n. hitherto Ambates cleroidesgeniculatus (Hustache, 1950) (Pardisomus), comb. n. hitherto Peridinetus geniculatusnigritarsis (Kuschel, 1958) (Pardisomus), comb. n. hitherto Agalmatus nigritarsispanamensis (Kuschel, 1958) (Pardisomus), comb. n. hitherto Agalmatus panamensispiazuroides (Voss, 1954) (Pardisomus), comb. n. hitherto Piazambates piazuroidesrufescens (Hustache, 1950) (Pardisomus), comb. n. hitherto Peridinetus rufescenssquamipes (Kirsch, 1857) (Pardisomus), comb. n. hitherto Scambus squamipessuffuscus Prena, 2003 (Pardisomus), spec. n.